2012
DOI: 10.1364/ao.51.008306
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of laser-induced breakdown spectroscopy spectra using a plastic optical fiber light collector and acoustic sensor device

Abstract: To estimate the acoustic plasma energy in laser-induced breakdown spectroscopy (LIBS) experiments, a light collecting and acoustic sensing device based on a coil of plastic optical fiber (POF) is proposed. The speckle perturbation induced by the plasma acoustic energy was monitored using a CCD camera placed at the end of a coil of multimode POF and processed with an intraimage contrast ratio method. The results were successfully verified with the acoustic energy measured by a reference microphone. The proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Wang et al presented three spectrum standardized methods in order to improve the reproducibility of LIBS measurements which are named the spectrum standardization approach [30], the sampled spectrum standardization approach [31] and the multivariate spectrum standardization method, respectively. In spectral standardization, a particular example is the use of acoustic signals [32,33] or laser-induced plasma image [34].…”
Section: Spectral Normalizationmentioning
confidence: 99%
“…Wang et al presented three spectrum standardized methods in order to improve the reproducibility of LIBS measurements which are named the spectrum standardization approach [30], the sampled spectrum standardization approach [31] and the multivariate spectrum standardization method, respectively. In spectral standardization, a particular example is the use of acoustic signals [32,33] or laser-induced plasma image [34].…”
Section: Spectral Normalizationmentioning
confidence: 99%
“…Yu et al reduced the spectral fluctuations using a gas mixture of helium (He), neon (Ne), and argon (Ar) as the surrounding ambiance. 14 The second one is to use assisted signals such as the speckle pattern, 15 acoustic signal, 16 and plasma images. 17,18 The third one is to correct spectral signals directly with algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the accuracy and consistency of LIBS measurement can be improved by adopting chemometrics techniques such as principal component analysis, partial least square, artificial neural network or support vector machine [14]. However, due to the complexity of these advanced chemometrics methods, normalization by the whole/partial spectral areas [15], acoustic wave [16], background emission [17], or internal standards [18] is more frequently used as an approach to improve the consistency in LIBS analysis. In our previous study [19], we reported that the intensity ratio of spectral lines of two different elements (e.g.…”
Section: Introductionmentioning
confidence: 99%